Paleoenvironmental and chronological analysis of the mammalian fauna from Migong Cave in the Three Gorges Area, China. (1st April 2017) - Pang, Libo; Chen, Shaokun; Huang, Wanbo; Wu, Yan; Wei, Guangbiao
Abstract: Migong Cave is an important Late Pleistocene fossil locality in the Three Gorges Area, and many mammalian fossils were excavated from this cave. The faunal characteristics of the small mammals from the Migong Cave are closest to the Oriental and the South China Region faunas, but also with some elements of the Himalaya-Hengduan Mountains Region and the Monsoon Region faunas. Most of the large mammals are typical members of the " Ailuropoda - Stegodon " fauna, but lack some common Late Pleistocene taxa of South China, such as Elaphas maximus, Rhinoceros sinensis, Cervus unicolor and Muntiacus . On the other hand, there are several large mammals of the Palaearctic Realm Pattern and the Monsoon Region Pattern in this locality. Through analyzing the features of the mammalian fauna and regional geomorphology, it is concluded that during the period of the Migong Cave fauna, seasonal temperature difference was obvious; the valleys were wider than the present; forests were relatively sparse, and the impact of the East Asian monsson was relatively strong. Combined with the isotope dating result, it is presumed that the age of Migong Cave is correlated to MIS 2. The unusual composition of the Migong Cave fauna challenges the past principle that the alternations of glacial period and interglacial period have no or very little influence on the mammalian fauna of Southwest China.